7C.08: STIFFNESS MODIFICATIONS ALONG AORTIC ARCH ARE DIFFERENT IN HYPERTENSIVES AND CONTROLS. (June 2015) - Rosenbaum, D.; Girerd, X.; Kachenoura, N.; De Cesare, A.; Cluzel, P.; Redheuil, A.
Abstract : Objective: Aortic Arch (AoA) stiffness has a major impact on blood pressure (BP). Our objectives were to assess the interplay between age, BP, stiffness and anatomy in normo and hypertensives. Design and method: AoA Cardiovascular MRI was performed. Ascending (AA), descending (DA) aortic diameters were calculated using automated segmentation of axial view acquired SSFP cine acquisition. AA and DA strains were calculated as (Systolic–Diastolic)/Diastolic areas and were used to calculate distensibility (Di): Di =strain/cPP where cPP is the central pulse pressure obtained by tonometry (sphygmocor ®). AoA-width (W) was the distance between the centre of AA and DA cross-sections. AoA height (H) defined the length of the orthogonal projection of the AoA centreline inflection point, positioned at the arch top, on the width of the AoA arch. AoA-length (L) was estimated using dedicated software as the distance between AA and DA locations used for strain measurements. Central BP was used to define BP levels. To evaluate relative changes between indices in the AA and in the DA, AA/DA diameters, strains and Di ratios were calculated. Figure. No caption available. Results: Population included 80 subjects (mean age 52 ± 13; 53% male): 23 normo and 57 treated hypertensives (28 controlled and 29 uncontrolled). Male proportion was 51%. Demographics were comparable in the 2 groups but all stiffness indices differed as well as L, W and all AA/DA stiffness indices ratios (table 1). Paired t-test in hypertensives showed that all AA and DA indices differed whereas in normotensives only diameters differed. In univariate analysis, AA/DA-diameters, AA/ DA-strain and AA/DA-Dis ratios all correlated to age, BP, height and gender. Moreover, stiffness ratios correlated to all anatomic indices especially AoA-L. Multivariate analysis with adjustment for age, gender, height, cSBP and AoA-L was performed in each group. In normotensives, AoA-L were independent correlates of AA/ DA stiffness ratios whereas in hypertensives, age and central systolic BP were significant determinant of relative stiffness changes between AA and DA. Conclusions: Stiffness modifications along the aortic arch correlate to morphologic parameters in normotensives whereas only age and BP were independent correlates in hypertensives